PERAN SATUAN POLISI PAMONG PRAJA DALAM PENERTIBAN PENGEMIS DAN GELANDANGAN BERDASARKAN PERATURAN DAERAH NOMOR 21 TAHUN 2008 TENTANG KETERTIBAN - Melannia Melannia; Emilda Firdaus; Zulwisman Zulwisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
According to Government Regulation (PP) Number 16 of 2018, Satpol PPis a regional apparatus formed to enforce Regional Regulations and Regional HeadRegulations, maintain public order and peace and provide community protection.The Civil Service Police Unit (Satpol PP) is an element that is always at theforefront in maintaining the mandate of Regional Regulations and is always indirect contact with the community. Based on the data obtained from the surveyresults from 2018 to 2020, beggars and homeless people in Indragiri Hilir Regencyare increasing, proving that there are still many homeless people and beggarsroaming Indragiri Hilir Regency.The purpose of this study was to determine the role of the civil servicepolice unit in controlling beggars and homeless people based on RegionalRegulation number 21 of 2008 concerning public order in Indragiri HilirThe role of the Civil Service Police Unit in controlling beggars andhomeless people based on Regional Regulation number 21 of 2008 concerningpublic order in Indragiri Hilir has not been implemented properly, because of thegap between legal regulations and what is happening in the field, The supportingand inhibiting factors in the implementation of this regional regulation are thesupporting factors, namely the policy factor itself, the Institutional Factor andImplementing Agency, and the environmental factor. The inhibiting factors arebudget factors, facilities and infrastructure factors and human resource factors.Efforts made by the Indragiri Hilir Regency government through the Civil ServicePolice Unit in controlling beggars and homeless Efforts made by the Indragiri HilirRegency government through the Civil Service Police Unit in controlling beggarsand homeless people are efforts that have been made by the Civil Service PoliceUnit in controlling beggars and homeless people, the efforts that will be made bythe Civil Service Police Unit in controlling beggars and homeless people and effortsbeing made by the Civil Service Police Unit in controlling beggars and homelesspeople.Keywords: beggars – vagabond..